Library Strategies in Improving Service Accessibility for Students with Intellectual Disabilities at SLB-E Negeri PTP Sumatera Utara - Putri Ramadhana; Yusniah Yusniah (AL Maktabah, 2026)
This study discusses library service strategies to improve accessibility for students with intellectual disabilities at PTP State Special Needs School for Education (SLB-E) in North Sumatra. This study is motivated by the importance of implementing inclusive library services that can meet the information needs of students with special needs. The purpose of this study is to analyze the implemented library service strategies and identify obstacles in providing accessible services for students with intellectual disabilities. The study used a descriptive qualitative method with data collection techniques through interviews, observation, and documentation. The results show that library service strategies are implemented through teacher mentoring, providing visual-based collections, simple literacy activities, and using communication approaches that are easy for students to understand. Teacher mentoring is the dominant strategy because students still need assistance in selecting and understanding reading materials. In addition, visual collections such as picture books are considered more effective in helping students understand information. This study also found obstacles such as limited facilities, a lack of adaptive collections, and the less than optimal role of librarians in disability services. This research contributes to the development of inclusive library studies, especially services.